Explaining Death to Young Children - Stickney, Doris; 1943-; Ortiz Hernandez, Gloria (Cleveland, OH, 1997)
After a water bug suddenly leaves her pond and is transformed into a dragonfly, her friends' questions about such departures are like those children ask when someone dies.
Keywords: Children; Religious aspects; Death; Death; Counseling of; Christian life